Design and implementation of microwave low noise amplifiers operating in the X band - Capiña, Mizpah T. (2011)
In this project, we aim to develop low noise amplifiers operating in the X band. With this, we are making a big step by entering the region of much higher frequencies in the field of microwave engineering. This project is all about designing two LNAs with two different transistors with same topology. The specifications of the amplifiers were dependent on the selected device models such as the RF transistor and DC bias circuits. The designs were simulated and implemented to test whether both LNAs are operating at 9 GHz which is part of the X-band spectrum. The amplifiers are tested and compared to determine the advantages and disadvantages of each design